PAINTING LOCAL WOOL FIBERS WITH SUFFERING SUBSTANCES (Euro-Asia Conferences, 2021)
The article presents the results of scientific research aimed atstudying the technology of dyeing woolen fabrics with irritants. Anaromatic hydroxylase phynocylose with an aromatic hydroxylase groupconsisting of an aromatic hydroxylase in the keratin macromolecule, whichis used as a nitrogen-fixing agent in the dyeing of cellulose fibers withwater-insoluble dyes in wool dye. The position of the color L *, a *, b * inthe color field is determined, and the color, saturation and brightness of thecolor depend on the environment of the dyeing process